Etnosains: Persepsi Calon Guru Kimia terhadap Pembelajaran Kontekstual Berbasis Budaya - Pandu Jati Laksono; Evelina A Patriot; Ari S Shiddiq; Resti Tri Astuti (Chemistry Education Department of Education and Teaching Faculty, 2023)
Ethno and science provide a dimension of togetherness in the development of society's culture and science. The aim of the study was to determine the perceptions of prospective chemistry teachers towards ethnoscience in contextual-based learning. The method used in this research is qualitative. Sources of data were taken from 39 first and second level chemistry teacher candidates and then specified into seven tribes in seven districts/cities in South Sumatra. The research instruments are surveys, interviews, and observations. Data were analyzed based on an interactive analysis model. The data analysis technique is to reduce the data and then draw conclusions. This study shows a positive perception of prospective chemistry teachers towards ethnoscience, that is, they are able to understand and elaborate on the ethnoscience approach in basic science lectures. The main problem faced by prospective chemistry teachers in the ethnoscience approach is that they are not used to connecting science content based on the chemical context with local culture. Ethnoscience approach can be implemented with Contextual Learning. This learning provides an opportunity for prospective chemistry teachers to further explore the culture of the surrounding community in a more real way. Contextual Learning helps and bridges the process of discovering concepts and contexts that exist in learning.